Effect of Caffeic Acid Phenethyl Ester on Vascular Damage Caused by Consumption of High Fructose Corn Syrup in Rats - Gun, Aburrahman; Ozer, Mehmet Kaya; Bilgic, Sedat; Kocaman, Nevin; Ozan, Gonca (Hindawi Ltd, 2016)
Fructose corn syrup is cheap sweetener and prolongs the shelf life of products, but fructose intake causes hyperinsulinemia, hypertriglyceridemia, and hypertension. All of them are referred to as metabolic syndrome and they are risk factors for cardiovascular diseases. Hence, the harmful effects of increased fructose intake on health and their prevention should take greater consideration. Caffeic Acid Phenethyl Ester (CAPE) has beneficial effects on metabolic syndrome and vascular function which is important in the prevention of cardiovascular disease. However, there are no known studies about the effect of CAPE on fructose-induced vascular dysfunction. In this study, we examined the effect of CAPE on vascular dysfunction due to high fructose corn syrup (HFCS). HFCS (6 weeks, 30% fed with drinking water) caused vascular dysfunction, but treatment with CAPE (50 micromol/kg i.p. for the last two weeks) effectively restored this problem. Additionally, hypertension in HFCS-fed rats was also decreased in CAPE supplemented rats. CAPE supplements lowered HFCS consumption-induced raise in blood glucose, homocysteine, and cholesterol levels. The aorta tissue endothelial nitric oxide synthase (eNOS) production was decreased in rats given HFCS and in contrast CAPE supplementation efficiently increased its production. The presented results showed that HFCS-induced cardiovascular abnormalities could be prevented by CAPE treatment.
Keywords: Insulin-Resistance; Blood-Pressure; Contractile Responses; Sweetened Beverages; Metabolic Syndrome; Enzyme-Inhibitor; Angiotensin-Ii; Weight-Gain; Hypertension; Reactivity